Bharavahaka figures as brackets above the pillar capital - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the pillar capital, the lintel above the pillar and the ceiling base in the mandapa (pillared hall) of the Neelkanth Mahadev Temple. The large pot-shaped moulding of the pillar is topped by a four-sided bracket. Above these brackets bharavahaka (load bearers) figures, there are small square sculptural panels. The lintel beams of the frame structure have friezes depiction fighting scenes and panels of deities.